Efficacy of Covid-19 Vaccines in Ethnically Diverse Population (BAME): A Systematic Review - Paul Wesley Thompson (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Black, Asian, and minority ethnic (BAME) groups are more prone to covid-19 disease severity and its associated mortality. The research has reported that the response of vaccines against different viral infections has varied among different groups of populations such as age, gender, race, and comorbidities. Therefore, the present study aimed to evaluate the efficacy of covid-19 vaccines of Emergency Use License (EUL) in BAME ethnicities. Method: We conducted a systematic review by using different names of EUL vaccines in Cochrane Covid-19 Study Register (CCSR) and WHO Covid‐19 global literature and exported the retrieved results to EndNote X8 to eliminate the duplicate records. The study followed PRISMA (Preferred Items for Reporting Systematic Reviews and Meta-analysis) guidelines for reporting systematic reviews. We descriptively reviewed the included studies and performed data synthesis for randomized controlled trials (RCTs). Results: A total of 4799 retrieved records were filtered down to 13 studies for inclusion which comprised nine RCTs, three case-control studies, and one retrospective cohort. The RCTs included in the data synthesis covered mRNA-1273, BNT162b2, NVX-CoV2373, AZD1222, and Ad26.COV2.S vaccines and reported 603 total events out of 125,874 participants in the interventional group and 3115 total events out of 109,093 participants in placebo groups. Compared to White participants, one RCT showed higher efficacy of mRNA-1237 in communities of color, whereas another RCT showed higher efficacy in Asians. Two RCTs showed that BNT162b2 had the highest efficacy (100%) in Black ethnicity. Similarly, one RCT of each NVX-CoV2373 and AZD1222 reported the highest efficacies of the respective vaccine in Black individuals. Among different vaccines, the Asian obtained the highest efficacy with mRNA-1273 but the lowest with BNT162b2. However, the data synthesis revealed a statistically significant favor for the efficacy of all vaccines over placebo across all subgroups of ethnicities. Conclusion: The covid-19 vaccines have non-inferior efficacy in different ethnicities. Nonetheless, the mRNA vaccines might be comparatively suitable for Black and Asian individuals in terms of efficacy than other vaccines. However, more studies with substantial representation of the BAME population are warranted to increase the magnitude of evidence in this regard. Keywords: Covid-19, vaccines, efficacy, BAME